Virtually Augmented Self-Hypnosis applied to endovascular interventions (VA-HYPO): Randomized Controlled Trial Protocol. - Salah D Qanadli; Louis Gudmundsson; Giuseppe Gullo; Alexandre Ponti; Sarah Saltiel; Anne-Marie Jouannic; Mohamed Faouzi; David C Rotzinger (PLoS ONE)
Endovascular interventions (EVI) are increasingly performed as minimally-invasive alternatives to surgery and have many advantages, including a decreased need for general anesthesia. However, EVI can be stressful for patients and often lead to anxiety and pain related to the procedure. The use of local anesthetics, anxiolytics, and analgesic drugs can help avoid general anesthesia. Nevertheless, these drugs have potential side effects. Alternative nonpharmacological therapies can improve patients' experience during conscious interventions and reduce the need for additional medications. The added value of virtually augmented self-hypnosis (VA-HYPO) and its potential to reduce pain and anxiety during peripheral and visceral arterial and venous EVI is unknown. This is a prospective two-arm trial designed to randomize 100 patients in two groups according to the use or not of VA-HYPO during peripheral EVI as a complementary nonpharmacological technique to improve patient comfort. The main objective is to compare per-procedural anxiety, and the secondary aim is to compare the rated per-procedural pain in both groups. The potential significance is that VA-HYPO may improve patients' experience during peripheral and visceral arterial and venous EVI and other minimally invasive interventions performed under local anesthesia. Trial registration: Our study is registered on clinicaltrials.gov, with trial registration number: NCT04561596.